Rancang Bangun Compact Automatic Tissue Processor dengan Arduino & Kontrol Suhu Realtime - Tegar Pandu Atmojo; Eko Nugroho; Setyo Adi Nugroho; Nita Yunianti Ratnasari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Automatic tissue processor is a tool used in pathological examinations. Processing complex tissue can be quite troublesome for operators if done manually, considering that the tissue processing stage requires precision and precise timing. To reduce time inaccuracies which can cause tissue sample results to be less than optimal, an Automatic Tissue Processor tool was created. However, the existing Automatic Tissue Processor tools are usually designed with a large shape so that reagent consumption during tissue processing is also large, this is an obstacle in some small anatomical pathology labs or small hospitals with few patients, besides that real-time temperature monitoring is rare. is in the tool so that the user often does not know what the real-time temperature is, causing control of the quality of the paraffin reagent to be difficult. Starting from this, using the research and development (RND) method, this research designed an automatic tissue processor with 4 Chambers, the last 1 Chamber being The paraffin Chamber is equipped with a Heater and temperature controller, using a DHT-22 temperature sensor. where the Chamber is made with a compact size so as to save on the use of reagents, the temperature in the Chamber is set at a cutoff temperature of 60o C. The research results show that the tool can work well for temperature sensor accuracy which is obtained at a value of 100% with an error rate of 0%, then for The Timer accuracy level was obtained at 99.57% with an error rate of 0.43%..